(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Anemia is one of the most consistent and severe hematological complication in chronic renal failure (CRF) patients. Lowered Hb concentration, packed cell volume (PCV) and total count (TC) of red blood cell (RBC) in such patients and the relation of changes of these values with the severity of renal failure is important to detect anemia earlier.. Subjects and Methods: The present study has been designed to observe hemoglobin concentration, PCV and TC of RBC in different stages of CRF patients suffering from anemia. For this purpose, 65 male CRF patients with anemia and 25 healthy male (control) subjects, age ranged from 3050 years were selected randomly from BSMMU outpatient department. Hb concentration, PCV, TC of RBC and creatinine clearance were estimated by usual laboratory technique. Data were analyzed statistically by ANOVA and Pearsons correlation coefficient test. Among 65 CRF patients, 15 were mild, 25 were moderate and 25 were severe with renal failure associated with anemia. Results: In this study, the mean Hb concentration, PCV and total count of RBCs were significantly lower in three stages of CRF patients with anemia compared to those of healthy subjects. Again, these hematological values were significantly (P < 0.001) lower in moderate and severe CRF patients compared to mild cases and also in severe cases than those of moderate CRF cases with anemia. All the hematological parameters showed positive correlation with creatinine clearance in three stages of CRF and it was statistically significant in moderate and severe group. Conclusion: From the present study it may be concluded that CRF patients with anemia had lower Hb concentration, PCV and TC of RBC and the degree of changes depend on severity of renal failure. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.36 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 31-34